PENGARUH PERBANDINGAN MINYAK KELAPA (Cocos nucifera) DENGAN LEMAK KAKAO (Theobroma cacao L.) DAN SUHU PEMANASAN TERHADAP KARAKTERISTIK SABUN - Sari, Ni Made Purindah; Wrasiati, Luh Putu; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
Soap is one of the cleansers made by chemical reactions between sodium or potassium bases with fatty acids from vegetable oils or animal fats, such as coconut oil, VCO, palm oil, castor oil, olive oil, soybean oil, cocoa fat, tallow and lard. The purpose of this study was to determine the effect of comparison of coconut oil with cocoa fat and heating temperature to the characteristics of soap and determine comparison of coconut oil with cocoa fat and heating temperature to produce the best soap characteristics. This study used factorial randomized block design with two factor experiments. The first factor was the comparison of coconut oil with cocoa fat which consists of five experimental levels, namely: 0:60, 15:45, 30:30, 45:15, 60: 0. The second factor was the heating temperature which consists of 3 experimental levels, namely: 60?C, 70?C, 80?C. The results showed that the comparison of coconut oil with cocoa fat and heating temperature and the interaction between the two treatments had a very significant effect (P<0.01) on rendemens, texture, and soap foam. Comparison of coconut oil with cocoa fat and heating temperature had a very significant effect (P<0.01), but the interaction between the two treatments had no significant effect (P>0.05) on soap water content. Comparison of coconut oil with cocoa fat was very significant (P<0.01), but the heating temperature and interaction between the two treatments had no significant effect (P>0.05) on free fatty acids and soap-free alkalis. The best treatment was obtained from an alternative treatment comparison of coconut oil with cocoa fat 15:45 and heating temperature 70?C with soap rendemens of 88.36%, soap texture of 4.90 kg, soap foam content of 72.64%, soap water content  of 13.73%, free fatty acid levels of 0.40 (ml equivalent NaOH/g), soap free alkalis of 0.05%. Keywords : Coconut oil, cocoa fat, heating temperature, saponification, soap